Peran Pertumbuhan Penjualan dalam Memediasi Pengaruh Profitabilitas dan Leverage terhadap Tax avoidance - Widati, Sindik; Sari, Dede Puspa; Rahayu, Vina Elfira; Hidayat, Taufik (E-Jurnal Akuntansi, 2024)
This study aims to investigate the role of company growth in mediating the effect of profitability and leverage on tax avoidance. Using data from mining companies listed on the Indonesia Stock Exchange, 92 research data from 23 companies and the period 2019-2022. The research method uses panel data regression analysis, and sobel test. The results showed that profitability has a significant negative effect on tax avoidance, while leverage does not show a significant effect. Firm growth did not prove to be a significant mediator in the relationship between profitability and tax avoidance, nor between leverage and tax avoidance. These findings suggest that factors other than firm growth may be more relevant in explaining how profitability and leverage affect tax avoidance strategies. Keywords: Tax avoidance; company growth; profitability; leverage